First results from a multiplexed and massive instrument with sub-electron noise Skipper-CCDs. (1st January 2023) - Chierchie, F.; Chavez, C.R.; Sofo Haro, M.; Fernandez Moroni, G.; Cervantes-Vergara, B.A.; Perez, S.; Estrada, J.; Tiffenberg, J.; Uemura, S.; Botti, A.
Abstract: We present a new instrument composed of a large number of sub-electron noise Skipper-CCDs operated with a two stage analog multiplexed readout scheme suitable for scaling to thousands of channels. New, thick, 1.35 Mpix sensors, from a new foundry, are glued into a Multi-Chip Module (MCM) printed circuit board on a ceramic substrate which has 16 sensors each. The instrument, that can hold up-to 16 MCMs, a total of 256 Skipper-CCD sensors (called a Super-Module with ≈ 130 grams of active mass and 346 Mpix), is part of the R&D effort of the OSCURA experiment which will have ≈ 94 super-modules. Experimental results with 10 MCMs and 160 Skipper-CCDs sensors are presented in this paper. This is already the largest ever built instrument with single electron sensitivity CCDs using nondestructive readout, both, in terms of active mass and number of channels.